Administration of α-Klotho Does Not Rescue Renal Anemia in Mice - Park, Min Young; Le Henaff, Carole; Sitara, Despina (Frontiers in Pediatrics, 2022)
Renal anemia is a common complication in chronic kidney disease (CKD), associated with decreased production of erythropoietin (EPO) due to loss of kidney function, and subsequent decreased red blood cell (RBC) production. However, many other factors play a critical role in the development of renal anemia, such as iron deficiency, inflammation, and elevated fibroblast growth factor 23 (FGF23) levels. We previously reported that inhibition of FGF23 signaling rescues anemia in mice with CKD. In the present study we sought to investigate whether -Klotho deficiency present in CKD also contributes to the development of renal anemia. To address this, we administered -Klotho to mice with CKD induced by an adenine-rich diet. Mice were sacrificed 24 hours after -Klotho injection, and blood and organs were collected immediately post-mortem. Our data show that -Klotho administration had no beneficial effect in mice with CKD-associated anemia as it did not increase RBC numbers and hemoglobin levels, and it did not stimulate EPO secretion. Moreover, -Klotho did not improve iron deficiency and inflammation in CKD as it had no effect on iron levels or inflammatory markers. Interestingly, Klotho supplementation significantly reduced the number of erythroid progenitors in the bone marrow and downregulated renal Epo and Hif2 mRNA in mice fed control diet resulting in reduced circulating EPO levels in these mice. In addition, Klotho significantly decreased intestinal absorption of iron in control mice leading to reduced serum iron and transferrin saturation levels. Our findings demonstrate that -Klotho does not have a direct role in renal anemia and that FGF23 suppresses erythropoiesis in CKD via a Klotho-independent mechanism. However, in physiological conditions -Klotho appears to have an inhibitory effect on erythropoiesis and iron regulation.